Rotavirus and the emergence of new genotypes: a narrative review (Revista Brasileira Multidisciplinar, 2020)
Rotavirus infection, which is directly related to the population’s quality of life, can culminate in death, mainly of children. This review discusses the prevalence and distribution of rotavirus genotypes, focusing on the genotypic variation of the virus after vaccines were implemented and cross-infection between animal and human species took place. We conducted a search of the literature from January 2006 to July 2017 by using the Web of Knowledge database and the search terms “rotavirus”, “genotype”, “prevalence post vaccine”, and “emerging genotypes”. The predominant genotypes changed in all the continents, and some genotypes are still emerging. There are two hypotheses for this global change: the genetics of the virus is variable, and vaccine-resistant genotypes have emerged. In addition, the virus can easily infect several animal species other than humans, as evidenced by reports of cross-infection of strains, which have served as a warning that new virus genotypes have been generated. Inter-sectoral actions that encompass not only the health sector, but also all the socio-economic sector including the government, researchers, teachers, health agents, and communities have contributed to reducing the health-related costs and mortality due to rotavirus infection, thereby improving health indicators and promoting health worldwide.
Keywords: Rotavirus; genotypes; vaccination; diarrhea